Sociometric Analysis Using the Sociogram Method to Determine The Quality of Student Friendship - Hardi Mahendra; Nono Heryana; Agung Susilo Yuda Irawan (Peneliti.net, 2022)
Soiogram is needed to get the final result of identification in themes, especially in friendship with students, in this modern era the pattern of friendship in students can affect the quality of learning and can affect the surrounding environment. Therefore, the author has analyzed the pattern of friendship with sociometry as one of the fields of science to determine the quality of friendship. By using a sociogram as the final result of the analysis, it is expected to be able to find out the cause of the bad friendship patterns of students.